Da divulgação científica à comunicação pública da ciência: trajetória da Universidade Federal de Uberlândia e propostas para a instituição - Malagoli, Daniela Avila (2019)
This research of the interdisciplinary professional masters in Technologies, Communication and Education of the Federal University of Uberlândia describes the trajectory of the Federal University of Uberlândia regarding to Public Communication of Science (CPC). It presents a bibliographic review on the CPC and related areas, such as Public Communication and Technoscience. It is assumed that the Public Communication of Science encompasses scientific dissemination but transcends that process with a view to the engagement, empowerment and autonomy of the subject, which is inevitably linked to science. The work continues a study already published in 2015 and presents a diagnosis of CPC in UFU and, therefore, the methodology includes journalistic interviews with members of the 2016-2020 management of the UFU and similar studies. The present research, when updating the institution's scenario, concludes that the UFU has signalized, since the beginning of the current superior administration, highly positive actions of CPC; and the university is, therefore, in a new setting. The study therefore constitutes theoretical reference on the subject and support material for the institution, with suggestions to complement the actions currently developed. Keywords: Public Communication of Science. Scientific divulgation. UFU. Engagement.